Sacred journeys in a modern world - Housden, Roger (Simon & Schuster Editions, 1998)
Sacred Journeys in a Modern World is a true story of the spiritual quest of a modern-day pilgrim. At the dawn of a new millennium, religion no longer holds a monopoly on what is considered sacred: we are all on a journey of discovery in which we are finding meaning for ourselves. Throughout his adult life, Roger Housden has regularly dropped his ordinary routine and gone walkabout in remote and urban regions of the globe. What makes a journey sacred for Roger Housden is not whether it follows some ancient pilgrim's path or leads to some holy shrine but whether it stirs our own authentic heart. It is sacred if it sensitizes the individual to the deeper realities of his own being and to the world about him.